Aquarium: an automatic data‐processing and experiment information management system for biological macromolecular crystallography beamlines. Issue 2 (14th March 2019) - Yu, Feng; Wang, Qisheng; Li, Minjun; Zhou, Huan; Liu, Ke; Zhang, Kunhao; Wang, Zhijun; Xu, Qin; Xu, Chuanyan; Pan, Qiangyan; He, Jianhua
Abstract : Aquarium is an automatic data processing and experiment information management system for synchrotron radiation source macromolecular crystallography beamlines. Aquarium is designed to automatically process data sets from data reduction to model building and results presentation. Users can monitor and inspect the data processing results from the Aquarium web site. Abstract : With the popularity of hybrid pixel array detectors, hundreds of diffraction data sets are collected at a biological macromolecular crystallography (MX) beamline every day. Therefore, the manual processing and recording procedure will be a very time‐consuming and error‐prone task. Aquarium is an automatic data processing and experiment information management system designed for synchrotron radiation source MX beamlines. It is composed of a data processing module, a daemon module and a web site module. Before experiments, the sample information can be registered into a database. The daemon module will submit data processing jobs to a high‐performance cluster as soon as the data set collection is completed. The data processing module will automatically process data sets from data reduction to model building if the anomalous signal is available. The web site module can be used to monitor and inspect the data processing results.